Про деякі особливості побудови інтелектуальних багаторівневих систем технічної діагностики електроенергетичних об'єктів - Мислович, М.В.; Сисак, Р.М. (Технічна електродинаміка, 2015)
Сформульовано вимоги до систем діагностування електроенергетичного обладнання з урахуванням концепції Smart Grid. Розроблено узагальнену структуру інтелектуальної розподіленої багаторівневої системи технічної діагностики електроенергетичного обладнання, яка відповідає основним вимогам концепції Smart Grid: двосторонній обмін інформацією між елементами системи та децентралізація обчислювальних ресурсів. Сформулированы требования к системам диагностирования электроэнергетического оборудования с учетом
концепции Smart Grid. Разработана обобщенная структура интеллектуальной распределенной многоуровневой
системы технической диагностики электроэнергетического оборудования, которая соответствует основным требования концепции Smart Grid: двусторонний обмен информацией между элементами системы и децент-
рализация вычислительных ресурсов. The main goal of the paper is development of structure of intelligent distributed multi-level system for technical
diagnostics of power electrical equipment. The discussed system implements the following general principles:
distribution of computational resources between different levels which is needed to support required periodicity of
measurements and signal processing; structuring of the diagnostic information on hierarchical principle; classification
of the diagnostic information by severity level for the optimization of information exchange. This structure of the
developed system complies with the basic requirements of the Smart Grid concept: bi-directional exchange of
information between system elements, and decentralization of computing resources. One possible implementation of the
system is discussed, which consists of 4 hierarchical levels typical to an average power plant. The structure represents
central diagnostic system, a number of local diagnostic systems and intelligent measuring devices. The paper details the
logic of data exchange between different hierarchical levels and their main functions.